1992
DOI: 10.1089/jir.1992.12.329
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Randomized Phase I Study on the Clinical Tolerance and Biological Effects of Natural and Recombinant Interferon-β

Abstract: The clinical tolerance of and the effects recombinant human interferon-beta (rHuIFN-beta) obtained from mammalian cells (Chinese hamster ovary cells) exerts on 2',5'-oligoadenyl (2-5A) synthetase activity, human-Mx protein, neopterin, beta 2-microglobulin, interleukin-1 (IL-1) alpha and beta synthesis were compared to those of natural IFN-beta in 12 healthy volunteers. Each subject received a single i.m. injection of 6 x 10(6) IU rHuIFN-beta and natural IFN-beta according to a randomized double-blind cross-ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, higher concentrations of r-IFN-b-1b are needed in vitro as compared to n-IFN or r-IFN-b-1a to obtain an isoeective cytotoxic or radiosensitizing eect. Interestingly, n-IFN and r-IFN-b1a have displayed similar pharmacokinetic properties in clinical studies (Liberati et al 1992;Salmon et al 1996). A comparative study on the pharmacokinetics of r-IFNb-1a and r-IFN-b-1b has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, higher concentrations of r-IFN-b-1b are needed in vitro as compared to n-IFN or r-IFN-b-1a to obtain an isoeective cytotoxic or radiosensitizing eect. Interestingly, n-IFN and r-IFN-b1a have displayed similar pharmacokinetic properties in clinical studies (Liberati et al 1992;Salmon et al 1996). A comparative study on the pharmacokinetics of r-IFNb-1a and r-IFN-b-1b has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study on healthy volunteers, recombinant IFN-b1b as compared to n-IFN-b induced similar changes in 2¢-5¢-adenylates, human Mx protein, and neopterin levels (Liberati et al 1992), which are considered to be the biochemical equivalent of the IFNaction. However, at present it is not clear whether the modulating action of IFNs on the radiation response is similar for natural as compared to recombinant IFNs.…”
Section: Introductionmentioning
confidence: 97%
“…That is the reason why we have explored possible changes in immunological parameters that may be more sensitive markers of cell activation. Indeed the expression of Mx protein in PBMC induced by IFNcx is a fairly long-lasting process [25,26] in comparison to cytokine's turnover. To our knowledge this is the first report showing that autohaemotherapy carried out with our procedure [21], i.e., …”
Section: Discussionmentioning
confidence: 99%
“…Most of the peaks occur earlier, i.e., at 48 hours, although the 5th peak is delayed by 72 hours. After a parenteral injection of either a or/3IFNs the Mx proteins peak occurs usually after 24 hours [25,26] but, after autohaemotherapy, PBMC, after homing in various organs, are likely to release IFN for 1-2 days therefore delaying the maximal expression of Mx proteins in circulating PBMC.…”
Section: Human Experimentsmentioning
confidence: 99%